Study regarding the correlation between the number of participants, the number of sports, and the number of countries participating in the summer Olympic Games - Ababe, R. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2018)
Sports are some of most dynamic social activities aimed to perfect the human being. For this reason, the specialists' preoccupation to periodically conduct prognosis analyses for spotting the sports' evolution tendencies, seems justified. This paper aims to emphasize the way in which the International Olympic Committee, through a positive policy and a good management has managed over the course of 114 years to become the largest international organization, surpassing from this point of view the United Nations. This study observed three components - the number of participants, the number of countries, and the number of sports in the program of the Olympic Games throughout time. The results of the research highlight the relatively ascendant evolution of the number of participants, with the mentioned syncopes, and the fact that the 241 participants in the first edition of the Olympics changed into 11238 participants in the last edition in 2016.